2022
DOI: 10.1002/ldr.4214
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and status of desertification in Central Asia

Abstract: Baseline determination is a prerequisite for desertification monitoring and assessment and also for the sustainable development of drylands. In this study based on long-term remote sensing net primary production (NPP) data and combined with a local NPP scaling method, the desertification status in Central Asia is quantified, and NPP-based objective baseline of desertification (potential NPP, NPP p ), which could be more convenient and enables the desertification status measurable from local to global scales, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(85 reference statements)
2
5
0
Order By: Relevance
“…Moreover, an 853.65 km 2 area in the study region also indicated a trend of desertification reversal. Our results are in line with Cai et al. (2022) , who reported a significant reversal of desertification within the Hotan oasis, as well as they also proposed PNPP as a benchmark for desertification research in Central Asia as we have used PNDVI as a benchmark for desertification assessment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, an 853.65 km 2 area in the study region also indicated a trend of desertification reversal. Our results are in line with Cai et al. (2022) , who reported a significant reversal of desertification within the Hotan oasis, as well as they also proposed PNPP as a benchmark for desertification research in Central Asia as we have used PNDVI as a benchmark for desertification assessment.…”
Section: Discussionsupporting
confidence: 91%
“…The comparison of PNDVI and ANDVI found that the distribution area of PNDVI with vegetation coverage greater than 15% in the study area increased by 2192.66 km 2 . Our findings are supported by Cai et al (2022), who reported that the natural vegetation in the desert oasis transitional zone in Hotan still has high growth potential. However, contrary to our findings, Pan and Xu (2020) reported that the vegetation coverage in Hotan is less than 60%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, we expected to find only limited coincidence between our soil‐specific results and generic “browning” maps, because most of the previous research considered “browning” as an overall decrease in vegetation indices, not an increase in soil presence, which is relatively sparse in Eurasia (Hu et al, 2020). As such, the detected pixel‐based changes in soil, gvsoil and gv+npvsoil fractions corresponded best with desertification in Central Asia and Kazakhstan arising from agricultural exploitation and climate change (Cai et al, 2022; Hu et al, 2020), and salinization (Robinson, 2016; UNEP, 2011). The high inter‐annual autocorrelation in the detected increase in soil fraction indicates the steadiness of desertification processes, presumably propelled by rising temperatures and aridity (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies suggested widespread grassland degradation and desertification in Eurasia (Cai et al, 2022; Hu et al, 2020; Zhang et al, 2018). However, our hypothesis tests found no significant map‐scale decrease in vegetation combined with an increase in the soil fraction (Table 3) even though our trend maps showed pixel‐level decrease in vegetation cover in favor of soil in Central Asia (gv+npvsoil,soil and gvsoil), and the Gobi Desert (gvsoil) (Figures 3, 4c, and 5b).…”
Section: Discussionmentioning
confidence: 99%